2018
DOI: 10.1111/pcn.12661
|View full text |Cite
|
Sign up to set email alerts
|

Ten‐year follow‐up study of Japanese patients with obsessive–compulsive disorder

Abstract: Our findings highlight the transcultural nature of long-term outcomes of OCD treatment, which appear to be independent of sociocultural differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The concept of recovery, widely addressed for other mental disorders such as depression, is underexamined in the OCD literature and requires concurrent attention Steketee, 2010, Sookman 2016;Mataix-Cols, et al 2016;Burchi et al 2018). It has been demonstrated that in response to treatments involving CBT alone and/or in combination with pharmacotherapy OCD is curable in some cases using criterion for recovery of score of ≤ 7 on the Yale-Brown Obsessive Compulsive Scale (YBOCS) plus psychosocial criteria (e.g., Sookman and Pinard, 1999;Sookman et al 2003;Simpson, et al 2006;Belloch et al 2008;Rachman et al 2015, Nakajima, 2018. Furthermore, achieving wellness at post treatment predicts stability of improvement (Elsner et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The concept of recovery, widely addressed for other mental disorders such as depression, is underexamined in the OCD literature and requires concurrent attention Steketee, 2010, Sookman 2016;Mataix-Cols, et al 2016;Burchi et al 2018). It has been demonstrated that in response to treatments involving CBT alone and/or in combination with pharmacotherapy OCD is curable in some cases using criterion for recovery of score of ≤ 7 on the Yale-Brown Obsessive Compulsive Scale (YBOCS) plus psychosocial criteria (e.g., Sookman and Pinard, 1999;Sookman et al 2003;Simpson, et al 2006;Belloch et al 2008;Rachman et al 2015, Nakajima, 2018. Furthermore, achieving wellness at post treatment predicts stability of improvement (Elsner et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To improve the long-term OCD symptoms and well-being of adults with OCD, we must determine potential predictors of adverse prognoses. Possible predictors of long-term OCD symptoms include being male (Eisen et al, 2010(Eisen et al, , 2013, being unmarried (Steketee et al, 1999;Van Oudheusden et al, 2018), earlier age at onset and longer duration of untreated OCD (Eisen et al, 2013;Perris et al, 2021), longer duration of OCD (Eisen et al, 2013;Fineberg et al, 2013;Van Oudheusden et al, 2018), greater severity of symptoms (Eisen et al, 2013;Van Oudheusden et al, 2018), lower global functioning (Steketee et al, 1999;Nakajima et al, 2018), family accommodation (Nakajima et al, 2018), and hoarding symptoms (Nakajima et al, 2018).…”
Section: Long-term Outcome Of Ocdmentioning
confidence: 99%
“…Over 40% of Japanese patients with OCD reported some involvement behaviors (IB) by their families to help or take part in their rituals, such as "asking family member for reassurance" (18). Such IB is a significant predictor of poor outcomes in OCD treatment (19). In the Japanese culture, an individual is expected to silently tolerate the anxiety experienced instead of verbally complaining.…”
Section: Introductionmentioning
confidence: 99%